(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Before dwelling on the process of dividing political parties in a state living in a democratic society into left, right and mediators, the history of the emergence and division of such types of parties, the differences, goals and actions of political parties and public organizations are noted.This is especially true of the activities of Asaba, one of the political parties that raised socio-economic issues, namely the provision of land for the construction of private houses.